Konteks Pendidikan Islam dalam Dimensi Tahannuts Pertemuan Pangeran Diponegoro dengan Sunan Kalijaga - El Syam, Robingun Suyud; Nugroho, Muhamad Yusuf Amin (MA'ALIM: Jurnal Pendidikan Islam, 2024)
The article attempts to reveal the context of Islamic education in the dimension of Prince Diponegoro's meeting with Sunan Kalijaga, where research on the spiritual dimension of Prince Diponegoro is rarely found. This research is a literature study setting using a qualitative approach. The research results show that Prince Diponegoro's meeting with Sunan Kalijaga in the Tahannuts dimension was a moral message for the Prince to mobilize the Javanese people to expel the Dutch colonial invaders and fight for the establishment of Islam in Java. The Tahannuts dimension is a spiritual experience in the supernatural aspect, not the real aspect. He experienced this spiritual experience by practicing penance by contemplating, tafakkur, remembering Allah, and purifying himself of all despicable qualities. Research implications regarding the importance of purifying oneself as part of serving God. Research is expected to contribute to Islamic education.